Advancement of the Cleavage Methods of Carbohydrate-derived Isopropylidene and Cyclohexylidene Ketals - Gupta, Shilpi; Sharma, Anjali; Mondal, Dhananjoy; Bera, Smritilekha (Current Organic Chemistry, 2022)
Carbohydrates, amino acids, and nucleosides, the fundamental building blocks of complex biomolecules in nature, are essential starting materials for the fabrication of natural and unnatural structural entities, which necessitate the masking and demasking of various functional groups with the utmost chemoselectivity, mildness, and efficiency to avoid unintended bond breaking and formation, as well as associated reactions. Ketals, benzylidene, methoxymethyl, p-methoxybenzyl, silyl ethers, trityl, tert-butyl carbamate, and other functional groups are widely used in modern organic synthesis. In carbohydrate chemistry, the commonly used protecting functionality of isopropylidene and cyclohexylidene ketals necessitates effective methods for selective cleavage. This review summarises different methods for deblocking isopropylidene and cyclohexylidene ketals using inorganic acids, Lewis acid, silica- supported inorganic acids, Amberlite-120 (H+) resin, phosphotungstic acid, Nafion-H, NaBArF4.2H2O, montmorillonite clay, Dowex 50W-X8, camphorsulphonic acid (CSA), ceric ammonium nitrate, molecular iodine, ionic liquids, zeolites and so on.
Keywords: Isopropylidene